Tibial Dyschondroplasia and Bone Mineral Density - ICL Almeida Paz (Revista Brasileira de Ciência Avícola, 2004)
This study was carried out at Faculdade de Medicina Veterinária e Zootecnia, UNESP, Botucatu-SP, Brazil. The aim was to establish the normal values of bone mineral density (BMD) expressed in millimeters of aluminum in the tibia of broiler chickens using optical densitometry of radiographs. Four hundred Cobb male chicks were reared from 1 to 40 days of age, when 40 of them were selected and the right femur-tibia articulation was radiographed. Radiographs were taken with the X-ray equipment calibrated for 45 kvp and 3.2 mAs and a focus-to-film distance of 90 cm. An aluminum phantom ASTM-6063 consisting of 20 ladder steps with graduate density was placed parallel to the area to be radiographed and used as a densitometry reference standard. Radiograph images were analyzed using the software ATHENA - SIA. The proximal growth plate of the right tibia epiphysis was used as the standard reading region. The inclination axis of the reading window was 0 and the window was 10 mm high and 40-45 mm wide, depending on the bone size. Optical densitometry values of the radiographs ranged from 1.46 to 1.77 mmAl, and the coefficient of variation was 9.93%. It was concluded that densitometry values beyond the range established in the present study might indicate the presence of bone alteration in the tibia of broilers.